A new leafhopper species of Maiestas Distant (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) from Thailand - Duan, Yani; Dietrich, Christopher H. (Zootaxa, 2017)
A new leafhopper species, Maiestas serrata sp.n., is described and illustrated from Thailand. This represents the first record of the genus from Thailand.